A method for removing impurities from lithium-ion battery leachate
By adopting a multi-step impurity removal method in the lithium-ion battery leaching liquid, combining iron raw materials, oxidants, fluorine-containing reagents and fluorine-removing materials, the effective removal of impurities in the lithium-ion battery leaching liquid has been successfully achieved, and the problem of difficulty in removing impurities and consuming a large amount of chemical reagents in the prior art is solved, and the purification effect and environmental protection are improved.
Patent Information
- Application Number
- CN202510258520.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the recycling of existing lithium-ion batteries, impurities in the leaching liquid are difficult to effectively remove, and the existing impurities removal methods are complex and consume a large amount of chemical reagents, resulting in secondary contamination.
By mixing the lithium-ion battery leaching liquid with iron raw materials, adjusting the pH value, copper and aluminum are removed, then mixing it with an oxidant to remove iron, then mixing it with a fluorine-containing reagent to remove calcium and magnesium, and using fluorine-depleting materials for fluorine ion adsorption, and finally mixing it with polymeric iron sulfate to remove phosphorus, so as to achieve purification of the leaching liquid.
While reducing the loss of valuable elements, this method effectively reduces the impurity content, reduces the consumption of materials during the impurity removal process, and avoids the generation of excessive waste liquid, improving environmental protection.
Smart Images

Figure CN119746510A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resource recovery, and in particular relates to a method for removing impurities from a lithium ion battery leachate. Background Art
[0002] Lithium-ion secondary batteries are a type of rechargeable chemical battery with good comprehensive performance. They have the advantages of high operating voltage, high specific energy, long cycle life, and low self-discharge. They are widely used in mobile communications, laptop batteries, portable tools, electric vehicles, etc. The positive electrode materials used in lithium-ion secondary batteries on the market are mainly lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and other binary / ternary materials containing lithium. These positive electrode materials all contain valuable metallic lithium resources.
[0003] Since lithium-ion batteries use a large amount of positive electrode materials and consume a lot of non-renewable metal resources, as the use of lithium-ion batteries increases day by day, recycling high-value and high-content metals in lithium-ion batteries is of great significance to achieving energy conservation, emission reduction and sustainable development.
[0004] At present, lithium-ion battery recycling usually adopts wet recycling, such as using sulfuric acid solution containing reducing agent to leach waste lithium-ion batteries to recover valuable metal elements such as nickel, cobalt, manganese, lithium, etc. However, impurities will inevitably enter the leachate during the leaching process, such as iron, aluminum, calcium, magnesium, copper, etc. Since there are many types of impurities in the leachate of waste lithium-ion batteries, it is necessary to remove them. The existing impurity removal methods are complicated and require a large amount of chemical reagents, thus causing secondary pollution. Summary of the invention
[0005] In view of this, the present invention provides a method for removing impurities from a lithium-ion battery leachate. The present invention generates by-products for subsequent impurity removal while removing impurities. The impurity removal method provided by the present invention further reduces the impurity content while reducing the loss of valuable elements; at the same time, the material consumption of impurity removal is reduced by recycling the regenerated fluorine removal material liquid; the impurity removal method provided by the present invention does not generate much waste liquid.
[0006] In order to solve the above technical problems, the present invention provides a method for removing impurities from a lithium ion battery leachate, comprising the following steps: The lithium ion battery leachate and the iron raw material are mixed, and the pH value of the system is adjusted to 3-5, and then copper and aluminum are removed, and copper-aluminum slag and a first liquid phase are obtained after a first solid-liquid separation; the impurities in the lithium ion battery leachate include one or more of copper ions, aluminum ions, iron ions, calcium ions, magnesium ions and phosphate ions; The first liquid phase and the oxidant are mixed, the pH value of the system is adjusted to 3-5, and then iron is removed, and polyferric sulfate and the second liquid phase are obtained after a second solid-liquid separation; The second liquid phase is mixed with a fluorine-containing reagent to remove calcium and magnesium, and a third solid-liquid separation is performed to obtain calcium-magnesium slag and a third liquid phase; The third liquid phase and the defluorination material are mixed to adsorb fluoride ions to obtain a fourth liquid phase and a loaded defluorination material; the loaded defluorination material is mixed with an alkaline solution to defluorinate to obtain a regenerated defluorination material; The fourth liquid phase is mixed with polyferric sulfate to remove phosphorus, and an iron-phosphorus complex and a purified leaching solution are obtained after the fourth solid-liquid separation.
[0007] Preferably, the iron raw material is iron powder, and the particle size of the iron powder is less than 500 μm; The molar ratio of the iron to the copper element in the lithium ion battery leachate is 1-2:1.
[0008] Preferably, the temperature for removing copper and aluminum is 50-95° C., and the time is 0.5-2 h; the process of removing copper and aluminum is accompanied by stirring, and the stirring speed is 100-300 r / min.
[0009] Preferably, the oxidant comprises hydrogen peroxide or sodium peroxide.
[0010] Preferably, the temperature of the iron removal is 50-95°C, and the time is 1-4 hours; the iron removal process is accompanied by stirring, and the stirring speed is 100-300 r / min; After obtaining the polyferric sulfate, the method further comprises: aging the polyferric sulfate; the aging time is 10 to 30 hours.
[0011] Preferably, the fluorine-containing reagent comprises sodium fluoride; The molar ratio of the total molar amount of calcium ions and magnesium ions in the lithium ion battery leachate to the fluorine-containing reagent is 1:2-3.
[0012] Preferably, the temperature for removing calcium and magnesium is 50-95°C and the time is 0.5-2h; The process of removing calcium and magnesium is accompanied by stirring, and the stirring speed is 100-300 r / min.
[0013] Preferably, the defluorination material comprises an ion exchange resin or an activated alumina defluorination agent; The alkaline solution includes a sodium hydroxide solution; When the defluorination material is an activated alumina defluorination agent, the defluorination temperature is 55-65°C and the time is 0.8-1.2h; the defluorination process is accompanied by stirring, and the stirring speed is 250-350r / min; When the defluorination material is an ion exchange resin, the third liquid phase is passed into the ion exchange resin for ion exchange; the flow rate of passing the third liquid phase into the ion exchange resin is 0.8-1.2 BV / h.
[0014] Preferably, the mass concentration of polyferric sulfate in the system after the fourth liquid phase and polyferric sulfate are mixed is 50-400 mg / L.
[0015] Preferably, the dephosphorization temperature is 50-95° C., and the time is 0.5-3 h; the dephosphorization process is accompanied by stirring, and the stirring speed is 100-300 r / min.
[0016] The invention provides a method for removing impurities from a lithium ion battery leachate, comprising the following steps: mixing the lithium ion battery leachate with an iron raw material, adjusting the pH value of the system to 3-5, removing copper and aluminum, and obtaining copper-aluminum slag and a first liquid phase after a first solid-liquid separation; the impurities in the lithium ion battery leachate include one or more of copper ions, aluminum ions, iron ions, calcium ions, magnesium ions and phosphate ions; mixing the first liquid phase with an oxidant, adjusting the pH value of the system to 3-5, removing iron, and obtaining polyferric sulfate and a second liquid phase after a second solid-liquid separation; mixing the second liquid phase with a fluorine-containing reagent, removing calcium and magnesium, and obtaining calcium-magnesium slag and a third liquid phase after a third solid-liquid separation; mixing the third liquid phase with a defluorination material, adsorbing fluoride ions, obtaining a fourth liquid phase and a loaded defluorination material; mixing the loaded defluorination material with an alkaline solution, defluorinating, and obtaining a regenerated defluorination material; mixing the fourth liquid phase with polyferric sulfate, removing phosphorus, and obtaining an iron-phosphorus complex and a purified leachate after a fourth solid-liquid separation. The impurity removal method provided by the present invention produces polyferric sulfate for phosphorus removal while removing iron, and achieves iron and phosphorus removal without increasing reagent consumption and steps. The present invention can use fluorine-containing reagents to ensure complete removal of calcium and magnesium while removing calcium and magnesium, and then use defluorination materials to remove excess fluorine. The defluorination materials used in the present invention can be reused in subsequent processes, reducing the consumption of defluorination materials. The impurity removal method provided by the present invention realizes material recycling while improving the purity of lithium-ion battery leachate, and does not generate excessive waste liquid, thereby improving environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the process of removing impurities from lithium-ion battery leachate in the embodiment. DETAILED DESCRIPTION
[0018] The present invention provides a method for removing impurities from a lithium ion battery leachate, comprising the following steps: The lithium ion battery leachate and the iron raw material are mixed, and the pH value of the system is adjusted to 3-5, and then copper and aluminum are removed, and copper-aluminum slag and a first liquid phase are obtained after a first solid-liquid separation; the impurities in the lithium ion battery leachate include one or more of copper ions, aluminum ions, iron ions, calcium ions, magnesium ions and phosphate ions; The first liquid phase and the oxidant are mixed, the pH value of the system is adjusted to 3-5, and then iron is removed, and polyferric sulfate and the second liquid phase are obtained after a second solid-liquid separation; The second liquid phase is mixed with a fluorine-containing reagent to remove calcium and magnesium, and a third solid-liquid separation is performed to obtain calcium-magnesium slag and a third liquid phase; The third liquid phase and the defluorination material are mixed to adsorb fluoride ions to obtain a fourth liquid phase and a loaded defluorination material; the loaded defluorination material is mixed with an alkaline solution to defluorinate to obtain a regenerated defluorination material; The fourth liquid phase is mixed with polyferric sulfate to remove phosphorus, and an iron-phosphorus complex and a purified leaching solution are obtained after the fourth solid-liquid separation.
[0019] The present invention mixes the lithium-ion battery leachate and the iron raw material, adjusts the system pH value to 3-5, removes copper and aluminum, and obtains copper-aluminum slag and a first liquid phase after the first solid-liquid separation. As a specific embodiment of the present invention, the lithium-ion battery leachate is obtained by leaching waste lithium-ion batteries with sulfuric acid combined with a reducing agent; the impurities in the lithium-ion battery leachate include one or more of copper ions, aluminum ions, iron ions, calcium ions, magnesium ions and phosphate ions; the mass concentration of iron ions in the leachate can be 1-5 g / L, specifically 1 g / L, 2 g / L, 3 g / L, 4 g / L or 5 g / L; the mass concentration of aluminum ions in the leachate can be 1-5 g / L , which can be specifically 1g / L, 2g / L, 3g / L, 4g / L or 5g / L; the mass concentration of copper ions in the leachate can be less than 1g / L, which can be specifically 0.5g / L; the mass concentration of calcium ions in the leachate can be less than 1g / L, which can be specifically 0.2g / L; the mass concentration of magnesium ions in the leachate can be less than 1g / L, which can be specifically 0.2g / L; the mass concentration of phosphate ions in the leachate can be less than 1g / L, which can be specifically 0.1g / L. As a specific embodiment of the present invention, the valuable elements in the lithium ion battery leachate can include one or more of nickel, cobalt, manganese and lithium, and can also be nickel, cobalt, manganese and lithium; the mass concentration of valuable elements in the lithium ion battery leachate can be 1~20g / L, and can also be 5~15g / L; the pH value of the lithium ion battery leachate is less than 0, which can be specifically -0.5 or -0.8.
[0020] As a specific embodiment of the present invention, the iron raw material can be iron powder, and the particle size of the iron powder can be less than 500 μm, and can be specifically 100 μm, 200 μm, 300 μm, 400 μm or 500 μm; the molar ratio of the iron to the copper element in the lithium ion battery leachate can be 1-2:1, and can be specifically 1.5:1 or 2:1. The present invention has no special limitation on the method of mixing the lithium ion battery leachate and the iron raw material, as long as they can be mixed evenly.
[0021] As a specific embodiment of the present invention, the lithium ion battery leachate and the iron raw material are mixed and then the pH value of the system is adjusted to 3-5, which can be specifically 3, 3.5, 4, 4.5 or 5. The present invention has no special limitation on the pH adjuster used to adjust the pH value of the system, as long as the pH value of the system can meet the requirements.
[0022] As a specific embodiment of the present invention, the temperature for removing copper and aluminum can be 50-95°C, specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, and the time for removing copper and aluminum can be 0.5-2h, specifically 0.5h, 1h, 1.5h or 2h; the process of removing copper and aluminum can be accompanied by stirring, and the stirring speed can be 100-300r / min, specifically 100r / min, 150r / min, 200r / min, 250r / min or 300r / min.
[0023] As a specific embodiment of the present invention, the copper and aluminum removal process may undergo reactions as shown in Formulas 1 to 3: Fe+Cu 2+ →Fe 2+ +Cu↓ Formula 1; CuSO4+H2O→Cu(OH)2↓+ H + Formula 2; Al 3 +3H2O→Al(OH)3+3H + Formula 3.
[0024] As a specific embodiment of the present invention, the first solid-liquid separation can be filtration; the copper-aluminum slag obtained by filtration is discharged. As a specific embodiment of the present invention, the copper-aluminum slag includes one or more of copper, copper hydroxide and aluminum hydroxide, and can be copper, copper hydroxide and aluminum hydroxide.
[0025] After obtaining the first liquid phase, the present invention mixes the first liquid phase with an oxidant and adjusts the pH value of the system to 3 to 5 before removing iron, and obtains polyferric sulfate and a second liquid phase after a second solid-liquid separation. As a specific embodiment of the present invention, the oxidant may include hydrogen peroxide or sodium peroxide; the present invention has no special restrictions on the content of the oxidant as long as it can oxidize divalent iron ions to trivalent iron ions. As a specific embodiment of the present invention, the mixing of the first liquid phase and the oxidant can be carried out under stirring, and the present invention has no special restrictions on the stirring as long as it can be mixed evenly.
[0026] As a specific embodiment of the present invention, after mixing the first liquid phase and the oxidant, the pH value of the system is adjusted to 3-5, which can be specifically 3, 3.5, 4, 4.5 or 5. The present invention has no special limitation on the pH adjuster used to adjust the pH value of the system, as long as the pH value of the system can meet the requirements.
[0027] As a specific embodiment of the present invention, the temperature of the iron removal can be 50~95°C, specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, the time of the iron removal can be 1~4h, specifically 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h; the iron removal process can be accompanied by stirring, and the stirring speed can be 100~300r / min, specifically 100r / min, 150r / min, 200r / min, 250r / min or 300r / min.
[0028] As a specific embodiment of the present invention, in the iron removal process, the oxidant oxidizes the divalent iron to trivalent iron and then reacts with sulfuric acid. Taking hydrogen peroxide as an oxidant as an example, the specific reaction is shown in Formulas 4 to 6: Oxidation reaction: 2FeSO4+H2O2+H2SO4→2Fe2(SO4)3+H2O (Formula 4); Hydrolysis reaction: 2Fe2(SO4)3+nH2O→Fe2(OH) n (SO4) 3-n / 2 +n / 2H2SO4 formula 5; Polymerization reaction: mFe2(OH) n (SO4) 3-n / 2 →[Fe2(OH) n (SO4) 3-n / 2 ] m Formula 6.
[0029] As a specific embodiment of the present invention, after obtaining the polyferric sulfate, the process may further include: aging the polyferric sulfate; the aging time may be 10 to 30 hours, specifically 10 hours, 15 hours, 20 hours, 24 hours or 30 hours; the aging temperature may be room temperature, and the room temperature may be 20 to 35° C., specifically 20° C., 25° C., 30° C. or 35° C. The present invention makes the particle structure of the polyferric sulfate more stable after aging, thereby extending its effective use time; and aging can improve the sedimentation performance of the polyferric sulfate.
[0030] As a specific embodiment of the present invention, the second solid-liquid separation may be filtration; the polyferric sulfate obtained by filtration is used for subsequent phosphorus removal.
[0031] After obtaining the second liquid phase, the present invention mixes the second liquid phase with a fluorine-containing reagent to remove calcium and magnesium, and obtains calcium-magnesium slag and a third liquid phase after a third solid-liquid separation. As a specific embodiment of the present invention, the fluorine-containing reagent may include sodium fluoride; the molar ratio of the total molar amount of calcium ions and magnesium ions in the lithium ion battery leachate to the fluorine-containing reagent may be 1:2-3, specifically 1:2, 1:2.5 or 1:3.
[0032] The present invention has no particular limitation on the manner of mixing the second liquid phase and the fluorine-containing reagent, as long as they can be mixed uniformly.
[0033] As a specific embodiment of the present invention, the temperature for removing calcium and magnesium can be 50-95°C, specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, and the time for removing calcium and magnesium can be 0.5-2h, specifically 0.5h, 1h, 1.5h or 2h; the process of removing calcium and magnesium can be accompanied by stirring, and the stirring speed can be 100-300r / min, specifically 100r / min, 150r / min, 200r / min, 250r / min or 300r / min.
[0034] As a specific embodiment of the present invention, the reaction occurring during the calcium and magnesium removal process is shown in Formulas 7 and 8: F - +Ca 2+ →CaF2↓ Formula 7; F - +Mg 2+ →MgF2↓ Formula 8.
[0035] As a specific embodiment of the present invention, the third solid-liquid separation may be filtration.
[0036] After obtaining the third liquid phase, the third liquid phase and the defluorination material are mixed to adsorb fluoride ions to obtain a fourth liquid phase and a loaded defluorination material. As a specific embodiment of the present invention, the defluorination material may include an ion exchange resin or an activated alumina defluorinator, and the material of the ion exchange resin may be a cross-linked polystyrene copolymer. The present invention utilizes the defluorination material to remove excess fluoride ions remaining in the third liquid phase. The present invention has no special limitation on the amount of the defluorination material, as long as the excess fluoride ions can be removed. As a specific embodiment of the present invention, when the defluorination material is an activated alumina defluorination agent, the temperature of the fluoride ion adsorption can be 45~55°C, specifically 45°C, 40°C or 55°C; the time of the fluoride ion adsorption can be 0.8~1.2h, specifically 1h; the process of the fluoride ion adsorption can be accompanied by stirring, and the stirring speed can be 150~250r / min, specifically 150r / min, 200r / min or 250r / min; when the defluorination material is an activated alumina defluorination agent, after the fluoride ion adsorption is completed, it can also include: filtering the system after the fluoride ion adsorption is completed to obtain the fourth liquid phase and the loaded defluorination material. As a specific embodiment of the present invention, when the defluorination material is an ion exchange resin, the third liquid phase is passed into the ion exchange resin for ion exchange; the flow rate of the third liquid phase into the ion exchange resin can be 0.8~1.2BV / h, specifically 1BV / h.
[0037] As a specific embodiment of the present invention, the loaded defluorination material and the alkaline solution are mixed for defluorination to obtain a regenerated defluorination material. As a specific embodiment of the present invention, the alkaline solution may include a sodium hydroxide solution; the mass concentration of the alkaline solution may be 2-4%; the pH value of the system after the loaded defluorination material and the alkaline solution are mixed may be 4-6, specifically 4, 5 or 6; the present invention has no special limitation on the amount of the alkaline solution, as long as the pH value of the mixed system meets the requirements.
[0038] As a specific embodiment of the present invention, the defluorination temperature can be 55-65°C, specifically 55°C, 60°C or 65°C; the defluorination time can be 0.8-1.2h, specifically 1h; the defluorination process can be accompanied by stirring, and the stirring speed can be 250-350r / min, specifically 250r / min, 300r / min or 350r / min.
[0039] As a specific embodiment of the present invention, the defluorination process may further include: filtering the defluorination system to obtain regenerated defluorination material and fluorine-containing alkali solution; the obtained fluorine-containing alkali solution can be used as a fluorine-containing reagent for removing calcium and magnesium, thereby achieving the reuse of waste liquid and improving environmental protection.
[0040] The present invention regenerates the loaded defluorination material through defluorination, thereby realizing the recycling of the defluorination material.
[0041] After obtaining the fourth liquid phase, the present invention mixes the fourth liquid phase with polyferric sulfate to remove phosphorus, and obtains an iron-phosphorus complex and a purified leachate after the fourth solid-liquid separation. As a specific embodiment of the present invention, the mass concentration of polyferric sulfate in the system after the fourth liquid phase and polyferric sulfate are mixed can be 50-400 mg / L, specifically 50 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 250 mg / L, 300 mg / L, 350 mg / L or 400 mg / L.
[0042] As a specific embodiment of the present invention, the dephosphorization temperature can be 50-95°C, specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, and the dephosphorization time can be 0.5-3h, specifically 0.5h, 1h, 1.5h, 2h, 2.5h or 3h; the dephosphorization process can be accompanied by stirring, and the stirring speed can be 100-300r / min, specifically 100r / min, 150r / min, 200r / min, 250r / min or 300r / min.
[0043] As a specific embodiment of the present invention, during the phosphorus removal process, polyferric sulfate will undergo two reactions with phosphate ions. First, polyferric sulfate and phosphate ions undergo a complex reaction to form a complex; then the complex further combines with the iron ions in the polyferric sulfate to generate an insoluble polyferric sulfate phosphorus precipitate.
[0044] As a specific embodiment of the present invention, the fourth solid-liquid separation may be filtration.
[0045] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0046] according to Figure 1 The process shown is for removing impurities from lithium-ion battery leachate.
[0047] Example 1 The lithium-ion battery leachate obtained by leaching waste lithium-ion batteries with sulfuric acid combined with a reducing agent was used as the treatment object. The contents of valuable elements in the lithium-ion battery leachate were as follows: the mass concentration of nickel was 40.56 g / L, the mass concentration of cobalt was 10.78 g / L, the mass concentration of manganese was 10.70 g / L, and the mass concentration of lithium was 7.66 g / L; the contents of impurity elements in the lithium-ion battery leachate were as follows: the mass concentration of copper ions was 0.21 g / L, the mass concentration of aluminum ions was 2.85 g / L, the mass concentration of iron ions was 3.2 g / L, the mass concentration of calcium ions was 0.24 g / L, the mass concentration of magnesium ions was 0.21 g / L, and the mass concentration of phosphate ions was 0.15 g / L; the pH value of the lithium-ion battery leachate was -0.79; The lithium-ion battery leachate and iron powder with an average particle size of 400 µm and a molar amount of twice the molar amount of copper ions in the lithium-ion leachate are mixed, and then the pH value of the system is adjusted to 4 using a sodium hydroxide solution with a mass concentration of 40%, and then stirred at a speed of 200 r / min at a temperature of 90° C. for 2 hours to remove copper and aluminum, and the copper-aluminum slag and the first liquid phase are obtained by filtering; The first liquid phase and 0.8 times the molar amount of ferrous iron in hydrogen peroxide (oxidant) were stirred and mixed, and the pH value of the system was adjusted to 4.0 using a 40% mass concentration of sodium hydroxide solution, and then the mixture was stirred at a temperature of 50°C and a speed of 200 r / min for 3 hours to remove iron, and the polyferric sulfate and the second liquid phase were obtained by filtration; the polyferric sulfate was placed at 30°C and aged for 24 hours; The second liquid phase is mixed with sodium fluoride (fluorine-containing reagent) whose molar amount is 2.5 times the total molar amount of calcium ions and magnesium ions in the lithium-ion battery leachate, and then stirred at a temperature of 90° C. and a speed of 300 r / min for 2 hours to remove calcium and magnesium, and the calcium-magnesium slag and the third liquid phase are obtained by filtering; The third liquid phase and an activated alumina defluorinating agent with a molar amount of fluorine element of 1.2 times are mixed at a temperature of 50° C. and stirred at a speed of 200 r / min for 1 hour to adsorb fluoride ions, and then filtered to obtain a fourth liquid phase and a loaded defluorinating material; The loaded defluorination material is slurried and mixed with a sodium hydroxide solution with a mass concentration of 4% to adjust the pH value of the system to 5, and then defluorinated at a temperature of 60°C and a speed of 300r / min for 1 hour, and the regenerated activated alumina defluorination agent and fluorine-containing alkali solution are obtained by filtration; the fluorine-containing alkali solution can be used as a fluorine-containing reagent for removing calcium and magnesium, and the regenerated activated alumina defluorination agent is used for subsequent fluoride ion adsorption; The fourth liquid phase and the matured polyferric sulfate were mixed (the mass concentration of polyferric sulfate in the mixed system was 200 mg / L) and then stirred at a speed of 100 r / min at a temperature of 50°C for 2 hours to remove phosphorus, and purified leachate and iron-phosphorus complex were obtained after filtration.
[0048] Example 2 The lithium ion battery leachate in Example 1 was used as the treatment object, the lithium ion battery leachate and the iron powder with a particle size of 300 μm and a molar amount of 1.5 times the molar amount of copper ions in the lithium ion leachate were mixed, and then the pH value of the system was adjusted to 4.5 using an alkali solution (40% mass concentration of sodium hydroxide), and then stirred at a speed of 300 r / min at a temperature of 90° C. for 1.5 hours to remove copper and aluminum, and filtered to obtain copper-aluminum slag and a first liquid phase; The first liquid phase and 0.6 times the molar amount of ferrous iron in hydrogen peroxide (oxidant) were stirred and mixed, and the pH value of the system was adjusted to 4.5 using an alkali solution (40% mass concentration of sodium hydroxide), and then the mixture was stirred at a speed of 300 r / min for 2 hours at a temperature of 80°C to remove iron, and the polyferric sulfate and the second liquid phase were obtained by filtration; the polyferric sulfate was placed at 30°C and aged for 30 hours; The second liquid phase is mixed with sodium fluoride (fluorine-containing reagent) whose molar amount is 3 times the total molar amount of calcium ions and magnesium ions in the lithium-ion battery leachate, and then stirred at 300 r / min for 2 hours at a temperature of 90° C. to remove calcium and magnesium, and filtered to obtain calcium-magnesium slag and the third liquid phase; Passing the third liquid phase into a cross-linked polystyrene copolymer ion exchange resin at a flow rate of 1 BV / h for ion exchange to obtain a fourth liquid phase and a fluorine-loaded ion exchange resin; A sodium hydroxide solution with a mass concentration of 4% is passed through a fluorine-loaded ion exchange resin at a flow rate of 1BV / h, with a dosage of 2BV; then washed with pure water at a flow rate of 10BV / h until the pH value of the effluent is between 6 and 7, to obtain a mixed solution of sodium fluoride and sodium hydroxide and a regenerated ion exchange resin; the fluorine-containing sodium hydroxide solution (mixed solution of sodium fluoride and sodium hydroxide) can be used as a fluorine-containing reagent for removing calcium and magnesium, and the regenerated ion exchange resin is used for subsequent fluoride ion adsorption; The fourth liquid phase and the matured polyferric sulfate were mixed (the mass concentration of polyferric sulfate in the mixed system was 150 mg / L) and then stirred at 200 r / min for 2 hours at a temperature of 60°C to remove phosphorus, and purified leachate and iron-phosphorus complex were obtained after filtration.
[0049] Example 3 The lithium ion battery leachate in Example 1 was used as the treatment object, the lithium ion battery leachate and the iron powder with a particle size of 200 μm and a molar amount of 2 times the molar amount of copper ions in the lithium ion leachate were mixed, and then the pH value of the system was adjusted to 3.5 using an alkali solution (40% mass concentration of sodium hydroxide solution), and then stirred at a speed of 300 r / min for 2 hours at a temperature of 90° C. to remove copper and aluminum, and filter to obtain copper-aluminum slag and a first liquid phase; The first liquid phase and 0.8 times the molar amount of ferrous iron in hydrogen peroxide (oxidant) were stirred and mixed, and the pH value of the system was adjusted to 3.5 with an alkali solution (40% mass concentration of sodium hydroxide solution), and then the mixture was stirred at a speed of 300 r / min for 2 hours at a temperature of 90°C to remove iron, and the polyferric sulfate and the second liquid phase were obtained by filtration; the polyferric sulfate was placed at 30°C for aging for 24 hours; The second liquid phase is mixed with sodium fluoride (fluorine-containing reagent) whose molar amount is 2.5 times the total molar amount of calcium ions and magnesium ions in the lithium-ion battery leachate, and then stirred at a temperature of 90° C. and a speed of 300 r / min for 2 hours to remove calcium and magnesium, and calcium-magnesium slag and the third liquid phase are obtained by filtering; The third liquid phase and an activated alumina defluorinating agent with a molar amount of fluorine element of 1.4 times are mixed at a temperature of 50° C. and stirred at a speed of 200 r / min for 1 hour to adsorb fluoride ions, and then filtered to obtain a fourth liquid phase and a loaded defluorinating material; The loaded defluorination material is slurried and mixed with a sodium hydroxide solution with a mass concentration of 4% to adjust the pH value of the system to 5, and then defluorinated at a temperature of 60°C and a speed of 300r / min for 1 hour, and the regenerated activated alumina defluorination agent and fluorine-containing alkali solution are obtained by filtration; the fluorine-containing alkali solution can be used as a fluorine-containing reagent for removing calcium and magnesium, and the regenerated activated alumina defluorination agent is used for subsequent fluoride ion adsorption; The fourth liquid phase and the matured polyferric sulfate were mixed (the mass concentration of polyferric sulfate in the mixed system was 200 mg / L) and then stirred at a speed of 100 r / min at a temperature of 50°C for 2 hours to remove phosphorus, and purified leachate and iron-phosphorus complex were obtained after filtration.
[0050] The impurity content in the purified leachate obtained by the treatment of Examples 1 to 3 was detected by inductively coupled plasma mass spectrometry (ICP-MS), and the results are listed in Table 1.
[0051] Table 1 Impurity content in the leaching solution before and after impurity removal in Examples 1 to 3
[0052] The fluoride ion content in the third liquid phase and the purified leachate in Examples 1 to 3 was detected by ICP-MS, and the results are listed in Table 2.
[0053] Table 2 Fluoride ion content in the third liquid phase and the purified leachate in Examples 1 to 3
[0054] It can be seen from Table 1 and Table 2 that the impurities can be well removed from the lithium-ion battery leachate after being treated by the impurity removal method provided by the present invention, and most of the by-products can be reused during the impurity removal process, greatly reducing the generation of waste.
[0055] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for removing impurities from a lithium ion battery leachate, comprising the following steps: The lithium ion battery leachate and the iron raw material are mixed, and the pH value of the system is adjusted to 3-5, and then copper and aluminum are removed, and copper-aluminum slag and a first liquid phase are obtained after a first solid-liquid separation; the impurities in the lithium ion battery leachate include one or more of copper ions, aluminum ions, iron ions, calcium ions, magnesium ions and phosphate ions; The first liquid phase and the oxidant are mixed, the pH value of the system is adjusted to 3-5, and then iron is removed, and polyferric sulfate and the second liquid phase are obtained after a second solid-liquid separation; The second liquid phase is mixed with a fluorine-containing reagent to remove calcium and magnesium, and a third solid-liquid separation is performed to obtain calcium-magnesium slag and a third liquid phase; The third liquid phase and the defluorination material are mixed to adsorb fluoride ions to obtain a fourth liquid phase and a loaded defluorination material; the loaded defluorination material is mixed with an alkaline solution to defluorinate to obtain a regenerated defluorination material; The fourth liquid phase is mixed with polyferric sulfate to remove phosphorus, and an iron-phosphorus complex and a purified leaching solution are obtained after the fourth solid-liquid separation.
2. The impurity removal method according to claim 1, characterized in that: The iron raw material is iron powder, and the particle size of the iron powder is less than 500 μm; The molar ratio of the iron to the copper element in the lithium ion battery leachate is 1-2:
1.
3. The impurity removal method according to claim 1 or 2, characterized in that: The temperature for removing copper and aluminum is 50-95° C., and the time is 0.5-2 hours. The process of removing copper and aluminum is accompanied by stirring, and the stirring speed is 100-300 r / min.
4. The impurity removal method according to claim 1, characterized in that: The oxidant includes hydrogen peroxide or sodium peroxide.
5. The impurity removal method according to claim 1 or 4, characterized in that: The temperature of the iron removal is 50-95°C, and the time is 1-4 hours; the iron removal process is accompanied by stirring, and the stirring speed is 100-300 r / min; After obtaining the polyferric sulfate, the method further comprises: aging the polyferric sulfate; the aging time is 10 to 30 hours.
6. The impurity removal method according to claim 1, characterized in that: The fluorine-containing reagent includes sodium fluoride; The molar ratio of the total molar amount of calcium ions and magnesium ions in the lithium ion battery leachate to the fluorine-containing reagent is 1:2-3.
7. The impurity removal method according to claim 1 or 6, characterized in that: The temperature for removing calcium and magnesium is 50-95°C and the time is 0.5-2h; The process of removing calcium and magnesium is accompanied by stirring, and the stirring speed is 100-300 r / min.
8. The impurity removal method according to claim 1, characterized in that: The defluorination material includes an ion exchange resin or an activated alumina defluorination agent; The alkaline solution includes a sodium hydroxide solution; When the defluorination material is an activated alumina defluorination agent, the defluorination temperature is 55-65°C and the time is 0.8-1.2h; the defluorination process is accompanied by stirring, and the stirring speed is 250-350r / min; When the defluorination material is an ion exchange resin, the third liquid phase is passed into the ion exchange resin for ion exchange; the flow rate of passing the third liquid phase into the ion exchange resin is 0.8-1.2 BV / h.
9. The impurity removal method according to claim 1, characterized in that: The mass concentration of polyferric sulfate in the system after the fourth liquid phase and polyferric sulfate are mixed is 50-400 mg / L.
10. The impurity removal method according to claim 1 or 9, characterized in that: The dephosphorization temperature is 50-95° C., and the time is 0.5-3 h. The dephosphorization process is accompanied by stirring, and the stirring speed is 100-300 r / min.
Citation Information
Patent Citations
Method for separating and recovering cobalt and nickel from manganese sulfate solution
CN110983054A
Harmless utilization method of lithium hexafluorophosphate in waste lithium ion battery electrolyte
CN111704151A
Two-stage fluorine removal method for fluorine-containing material
CN112267023A
Method for preparing lithium carbonate and ternary precursor by recycling waste ternary lithium battery
CN112374511A
Waste battery combined regeneration treatment method
CN112670610A
Cited By
Extraction and impurity removal method for transition metal solution
CN122128550A
Process for the extraction of impurities from a transition metal solution
CN122128550B